Novel proteomic molecular signatures of brain endothelial cells and microglia in the aging mouse brain: Developing topics. (7th December 2020) - Rayaprolu, Sruti; Duong, Duc; Xiao, Hailian; Carter, Emma Kathleen; Cheng, Lihong; Levey, Allan I; Seyfried, Nicholas T; Rangaraju, Srikant
Abstract: Background: Immune and vascular mechanisms of aging and Alzheimer's disease (AD) are mediated by microglia and endothelial cells, respectively. Transcriptomic studies of endothelial cells and microglia have revealed distinct and overlapping molecular features between these cell types while brain endothelial proteomic signatures remain unknown. Using concurrent isolation of microglia and endothelial cells from adult mouse brain along with multiplex quantitative proteomics, we contrast the proteomic profiles of these cell‐types and define their unique age‐related proteomic characteristics, for the first time. Method: The study cohort consisted of 3 and 7‐month‐old C57BL/6J mice ( N = 6/age, 3M and 3F). Endothelial cells and microglia were concurrently isolated from fresh, whole mouse brain using fluorescence‐activated cell sorting (FACS). On average, 14, 000 endothelial cells and 20, 000 microglia were sorted directly into 8M urea and digested. Peptides from each sample were randomized into four batches and labeled using 16‐plex tandem‐mass‐tag (TMT) kits. After high pH fractionation, peptides were analyzed by liquid chromatography‐tandem mass spectrometry (LC‐MS/MS) with synchronous precursor selection MS3 based quantification (SPS‐MS3). Raw files were processed using Proteome Discoverer. The spectra were searched against UniProt mouse proteome database. Differential expression analysis and Gene Ontology analysis (GO) was performed. Result: Quantitative proteomics of endothelial cells and microglia from adult mice identified 512 proteins. Of these, 199 proteins differentiated microglia from endothelial cells (Fig.1A) of which 20 proteins had >4‐fold higher expression in microglia (e.g., Rgs10) and 60 proteins had >4‐fold higher expression in endothelial cells (e.g., Hspa12b). 51 proteins demonstrated age‐dependent changes in microglia (Fig. 1B; 18 increased and 33 decreased). 35 proteins demonstrated age‐dependent changes in endothelial cells (Fig.1B; 15 increased and 20 decreased). GO analysis showed age‐dependent increase in structural, morphogenesis, and intermediate filament proteins and decrease in cell motility and macromolecular biosynthetic proteins in microglia. Age‐dependent changes in endothelial cells included increased gene transcription, splicing, and subcellular transport and decrease in chromatin organization and cytokine production proteins. Conclusion: In this direct comparison of proteomic profiles of adult mouse microglia and endothelial cells, we report proteomic signatures that differentiate microglia and endothelial cells and identify unique age‐dependent changes in microglia and endothelial cells.